Employees Participation is essential in every Organization why? - Annakili, P (International Journal of Psychosocial Rehabilitation, 2020)
–King slave relationship will never be an effective for all the organization. Slave type of relationship does not yield maximum output from employees. The maximum output will be delivered by the happy employees. Organisation can think that how they make employees happy? The organisation should give suitable salary, respect, good working environment, welfare facilities etc. Salary is first essential factor to make employees happy. But salary does not give full happiness, second one respect. Respect comes only in the form of employees’ participation. In this paper we will discuss why employees’ participation is essential one. It is a literature review paper